Energy landscape description of the clustering transition for active soft spheres - Maiti, Moumita; Schmiedeberg, Michael (EPL - Europhysics Letters, 2019)
For a system consisting of active soft spheres in three dimensions, we study the transition from a fluid where overlaps between particles can only occur for a short time after a collision to a state where clusters of overlapping particles persist for a long time. In order to determine the properties of the transition, we explore the energy landscape of the system in a similar way as it is done for the determination of the athermal or thermal jamming transition. Note that for zero temperature the competition of particles that attach to existing clusters and particles that detach due to thermal effects does not arise. Therefore, here we do not study such a competition because we consider systems at small or zero energy. Instead, we explore at which packing fractions and what activities cluster formation can occur at all. In case of an athermal system the transition between systems where no clusters develop at all and systems where stable clusters are found is a first order transition for packing fractions below 0.55 while the transition is continuous in case of larger packing fractions. In case of thermal systems the transition is continuous everywhere. While our approach does not deal with the real dynamics of the system, it reveals the nature of the clustering transition and it enables a deeper insight in the consequences of thermal fluctuations and the relation of the clustering transition to jamming. Though Brownian timescales diverge in athermal systems, the activity that we consider can be compared to the active velocity in other simulations if the later is measured in units of the particle size divided by an elastic time scale.<br
Keywords: active particles clustering transition jamming

Ergodicity breaking transition in a glassy soft sphere system at small but non-zero temperatures - Maiti, Moumita; Schmiedeberg, Michael (Scientific Reports, 2018)

Temperature dependence of the transition packing fraction of thermal jamming in a harmonic soft sphere system - Maiti, Moumita; Schmiedeberg, Michael (Journal of Physics: Condensed Matter, 2019)
The glassy dynamics of soft harmonic spheres are often mapped onto the dynamics of hard spheres by considering an effective diameter for the soft particles and therefore an effective packing fraction. While in this approach the thermal fluctuations within valleys of the energy landscape are covered, the crossing of energy barriers from one valley into another usually is neglected. Here we argue—motivated by studies of the glass transition based on explorations of the energy landscape—that the crossing of energy barriers can be attributed by an effective decrease of the glass transition packing fraction with increasing temperature T according to T 0.2. Furthermore, we reanalyzing data of soft sphere simulations. Since fitting scaling laws to simulation data always allows for some arbitrariness, we cannot prove based on the simulation data that our idea of a shift of the glass transition packing fraction due to barrier crossings is the only possible way to explain the discrepancies that have been observed previously. However, we show that a possible explanation of the simulation data is given by our approach to characterize the dynamics of soft spheres by both, the previously-considered temperature-dependent effective packing fraction due to the increase of the mean overlap between neighboring particles with stronger thermal fluctuations and the newly introduced increase of the glass transition packing with an increasing probability of barrier crossing
Keywords: glass transition; jamming; colloids

The thermal jamming transition of soft harmonic disks in two dimensions - Maiti, Moumita; Schmiedeberg, Michael (European Physical Journal E, 2019)
By exploring the properties of the energy landscape of a bidisperse system of soft harmonic disks in two dimensions we determine the thermal jamming transition. To be specific, we study whether the ground state of the system where the particle do not overlap can be reached within a reasonable time. Starting with random initial configurations, the energy landscape is probed by energy minimization steps as in case of athermal jamming and in addition steps where an energy barrier can be crossed with a small but non-zero probability. For random initial conditions we find that as a function of packing fraction the thermal jamming transition, i.e. the transition from a state where all overlaps can be removed to an effectively non-ergodic state where one cannot get rid of the overlaps, occurs at a packing fraction of φ_G=0.74, which is smaller than the transition packing fraction of athermal jamming at φ_J=0.842. Furthermore, we show that the thermal jamming transition is in the universality class of directed percolation and therefore is fundamentally different from the athermal jamming transition.<br
Keywords: Jamming Glass Transition